Isolated transfusion of leucocyte-depleted apheresis platelet concentrates and outcomes after cardiac surgery. (16th August 2017) - Koster, Andreas; Zittermann, Armin; Birschmann, Ingvild; Gummert, Jan
Abstract: We investigated the association of isolated leucocyte-depleted single-donor apheresis platelet concentrate transfusion with short- and long-term outcomes of patients undergoing isolated or combined coronary artery bypass and valve surgery. Propensity score matching was used to compare the results of patients without blood product transfusion and patients with isolated platelet transfusion ( n  = 167 per group). The primary end-point was a composite of operative complications. Additionally, we assessed coronary reintervention and overall mortality over a follow-up period of 7.5 years. In the platelet− and platelet+ groups, the composite end-point was reached at 9.6% and 12.3%, respectively ( P  = 0.307). None of the patients died within 30 days. None of the patients needed coronary reintervention during follow-up. Long-term mortality was similar between groups ( P  > 0.05). Isolated leucocyte-depleted apheresis platelet transfusion does not appear to be associated with an increase in morbidity or mortality in non-complex cardiac surgery. However, larger studies are needed.